Preparation and dielectric properties of lead-free perovskite-structured high-entropy ceramics of (La0.25Sr0.25Ba0.25Na0.25)(Ti0.5Me0.5)O3-δ (Me=Sn, Zr, Hf) via doping at both A and B sites. Issue 1 (1st January 2023) - Chen, Yingquan; Li, Rui; Zhang, Yan; Long, Yanping; Liu, Na; Xia, Haijun; Luo, Xiong; Meng, Bin
Abstract: A series of lead-free perovskite-structured high-entropy dielectric ceramics with a composition of (La0.25 Sr0.25 Ba0.25 Na0.25 )(Ti0.5 Me0.5 )O3 (Me = Sn, Zr, Hf) were designed by doping at both the A and B sites. Specifically, these ceramics were prepared via a solid-state reaction method combined with conventional sintering at 1500  ° C for 10 h. All high-entropy ceramics were consisted of a perovskite-structured single solid solution with an average grain size of 2.78–3.85 μm. Of the three samples, (La0.25 Sr0.25 Ba0.25 Na0.25 )(Ti0.5 Sn0.5 )O3 exhibited the highest dielectric constant, which remained stable from in 25–312  ° C. All three groups of high-entropy ceramics showed typical relaxor behaviour. The discharge energy density ( W d  = 0.31 J/cm 3 ), energy storage efficiency ( η  = 90.88%) and breakdown strength ( BDS  = 300 kV/cm) of (La0.25 Sr0.25 Ba0.25 Na0.25 )(Ti0.5 Sn0.5 )O3 were much higher than those of BaTiO3 ( W d  = 0.08 J/cm 3, η  = 46.09%, BDS  = 30 kV/cm) and other reported lead-free dielectric ceramics. These results demonstrate that high-entropy (La0.25 Sr0.25 Ba0.25 Na0.25 )(Ti0.5 Me0.5 )O3 ceramics are promising new candidates for high-performance, lead-free dielectric ceramics.